Analysis of historical content in al-Kamil fi al-Tarikh according to Ibn al-Athir / Abdul Qayuum Abdul Razak … [et al.] - Abdul Razak, Abdul Qayuum; Jamaludin, Norsaeidah; Meerangani, Khairul Azhar; Mohd Fadzil, Muhammad Faidz; Saja @ Mearaj, Ijlal; Mohamad Rohana, Noor Aziera (Academy of Contemporary Islamic Studies (ACIS), 2021)
This article discusses the analysis of historical content in the book of al-Kamil fi al-Tarikh according to Ibn al-Athir. It also briefly highlights the biography of Ibn al-Athir. In addition, this article also discusses the periodization analysis and the historical theme used by Ibn al- Athir in his book. The research method uses inductive and deductive approaches as well as historical studies. The result found that the analysis of periodization is arranged in chronological order. Besides, analysis on the historical theme of this book can be categorized into two namely; universal covering the pre-Islamic history to the time of ‘Abbasid Caliphate and contemporary covering the history of Zangid Dynasty and the present.